Changing Economic Problems for Women in the Nile Perch Fishing Communities on Lake Victoria - Médard, Modesta; Wilson, Douglas C. (Anthropologica, 2022)
Large-scale changes in the ecology of Lake Victoria have had a number of implications for the women in riparian households. It has proven difficult for them to take advantage of the economic opportunities that have arisen while their access to the lake fisheries has been diminished. This article reviews these changes at the levels of the lake, the community and the household. Fish-related economic activities are particularly important for women who are heads of households. These activities also afford married women greater independence than other activities. Women are responding to changes in access to the lake by working together at a community level.